Design and Implementation of Information Service System of Hunan Regional Seismic Network. Issue 3 (March 2021) - Tang, Hongliang; Zhang, Yimei; She, Xuming; Kang, Chengxu; Tian, Youping
Abstract: In this paper, the framework of one-stop application service system of Hunan Regional Seismological Network is introduced, taking the fast earthquake reporting of Hunan Regional Seismological Network as an example, in order to realize the automatic, one-stop application service of graphic and text data display, which integrates "obtaining earthquake parameters-issuing earthquake message-completing website earthquake situation update-automatically sending fax".